Draft Genome Sequence of Sinorhizobium meliloti Strain CXM1-105 - Baturina, Olga A. (Microbiol Resour Announc, 2019)
Sinorhizobium meliloti is a Gram-negative bacterium which fixes atmospheric nitrogen in symbiosis with Medicago spp. We report the draft genome sequence of S. meliloti strain CXM1-105, associated with nodules of Medicago sativa subsp. varia (Martyn) Arcang.